Cigarette smoke affects apoptosis in rat tongue mucosa: Role of bcl-2 gene family - Assis, Gerson F.; Ceolin, Daniele S.; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Daniel A. (Springer, 2005)
While it has been clearly demonstrated that smoking is the most significant exogenous factor involved in oral carcinogenesis, little is known about the global molecular and cellular changes that occur prior to the appearance of clinically detectable symptoms. Thus, the aim of this study was to investigate the expressivity of bcl-2, bax and PCNA in the rat tongue mucosa exposed to cigarette smoke by means of immunohistochemistry. A total of twelve male Wistar rats were distributed into 2 groups: negative control and experimental group exposed to cigarette smoke during 75 days. After experimental period, no histopathological changes in the tongue mucosa were detected in the negative control and the experimental group. on the other hand, an overexpression of bcl-2 was detected (p < 0.01) throughout all layers of the epithelium, whereas bax did not show significant differences (p > 0.05). Also, the labeling index for bcl-2 and bax showed an increase 75 days after cigarette exposure (p < 0.01). PCNA-labeling index did not show remarkable changes between groups. Taken together, our results show that bcl-2 is overexpressed in the rat tongue keratinocytes after cigarette smoke exposure.
Keywords: bax; bcl-2; PCNA; rat tongue; smoking